25 Nitric Oxide-cGMP Signalling Promotes B-Catenin Nuclear Translocation and Transcriptional Activity in Endothelial Cells. (19th January 2014) - Warboys, C M; Chen, N; Zhang, Q; Shaifta, Y; Vanderslott, G; Passacquale, G; Hu, Y; Xu, Q; Ward, J P T; Ferro, A
Abstract : Nitric oxide (NO) derived from endothelial NO synthase (eNOS) exerts cardioprotective effects. eNOS binds to a number of proteins that regulate its function. Using mass spectroscopy to study eNOS immunoprecipitated from human umbilical vein endothelial cells (HUVEC), we identified β-catenin as a novel binding partner of eNOS. This previously unrecognised interaction was confirmed by western blot analyses of both eNOS and β-catenin immunoprecipitates. Further, eNOS activation (using adenosine, salbutamol, histamine or thrombin), application of an NO donor (spermine NONOate) or elevation of cGMP (using sildenafil or 8-bromo-cGMP) all increased nuclear translocation of β-catenin. Nuclear β-catenin activates T cell factor (TCF)/lymphoid enhancing factor (LEF) transcription factors. Application of spermine NONOate or elevation of cGMP increased β-catenin transcriptional activity, as assessed using a luciferase reporter assay in HUVEC transfected with TCF/LEF reporter plasmids. The role of β-catenin in regulating NO-mediated angiogenesis was assessed in wild type and β-catenin-/- mouse pulmonary endothelial cells (MPECs) using an in vitro Matrigel assay. Stimulation with vascular endothelial growth factor (VEGF; NO dependent), spermine NONOate or cGMP elevation increased tube length compared to untreated controls in wild type but not β-catenin-/- MPECs, although both exhibited similar responses to basic fibroblast growth factor (NO independent). Similarly, in C57BL/6 mice, subcutaneous Matrigel plugs containing VEGF and β-catenin siRNA contained fewer endothelial cells compared to plugs containing scrambled siRNA. We conclude that activation of NO-cGMP signalling induces nuclear translocation of β-catenin, which promotes angiogenesis. Whether this contributes to other physiological processes involving NO-mediated transcription remains to be determined.